United States Constitution collection
Reports, notes, journals, letters, memoranda, and printed items documenting the drafting of the U.S. Constitution, the Constitutional Convention (1787), and proposals relating to the Bill of Rights and subsequent amendments to the Constitution. Includes manuscript of the Bill of Rights (1789) signed by Frederick Augustus Conrad Muhlenberg and John Adams. Includes material by Abraham Baldwin, David Brearley, Nicholas Gilman, Jared Ingersoll, Rufus King, James Madison, Edmund Pendleton, and George Washington.
Chiefly photocopies and facsimiles of originals in various repositories, including the Library of Congress.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826.; Baldwin, Abraham, -- 1754-1807.; Brearly, David, -- 1745-1790.; Gilman, Nicholas, -- 1755-1814.; Ingersoll, Jared, -- 1749-1822.; King, Rufus, -- 1755-1827.; Madison, James, -- 1751-1836.; Muhlenberg, Frederick Augustus Conrad, -- 1750-1801.; Pendleton, Edmund, -- 1721-1803.; Washington, George, -- 1732-1799.; United States; United States; United States. -- Constitutional Convention -- (1787)